Application of two‐dimensional liquid chromatography in the separation of traditional Chinese medicine. Issue 1 (25th November 2019) - Zhou, Weijia; Liu, Yanming; Wang, Jixia; Guo, Zhimou; Shen, Aijin; Liu, Yanfang; Liang, Xinmiao
Abstract: Traditional Chinese medicines have been widely used to prevent and cure diseases for thousands of years. For the purpose of better understanding the extremely complicated traditional Chinese medicines, powerful separation techniques are essential. Two‐dimensional liquid chromatography has been proven to be more powerful for the separation of complex traditional Chinese medicines due to its enhanced peak capacity and resolution compared with one‐dimensional liquid chromatography. Enormous efforts have been made on the coupling of independent separation mechanisms to improve the resolving power for complex traditional Chinese medicine samples, including the development and introduction of novel stationary phases. This review aims to give an overview on the applications of two‐dimensional liquid chromatography in traditional Chinese medicine research since 2008, including comprehensive two‐dimensional liquid chromatography, heart‐cutting two‐dimensional liquid chromatography both in on‐line, and off‐line mode. Different couplings of separation modes were respectively discussed based on specific studies, with emphasis on the applications of novel stationary phases in the two‐dimensional liquid chromatography.